(untitled) (Journal of Social Sciences Review, 2023)
Multicultural education is increasingly vital for equity in different classrooms. This study examines intercultural education’s pros and cons from teachers’ and students’ perspectives. This study used easy sampling to choose 200 individuals from Lahore, Punjab educational institutions. Multicultural education promotes cultural awareness, empathy, and respect in pupils, which can improve diversity. Multicultural education improves critical thinking, brainstorming, and problem-solving in the classroom. Multicultural education enabled teachers and students to understand and appreciate diverse cultures, faiths, and languages and challenge their assumptions to see the world from different perspectives. Multicultural education also fosters camaraderie in varied classrooms. Multicultural education improved student connections and classroom inclusion. The study also found that teachers feel unprepared to teach in diverse classrooms and lack the resources to effectively integrate multicultural education. Students also say intercultural education overloaded information access. Some also view intercultural education as useless and uncomfortable since it discusses sensitive themes like culture and identity. This research reveals intercultural education’s benefits and drawbacks in creating equality in heterogeneous classrooms. Further, instructors need more assistance and training to promote and execute multicultural education in classrooms and offer students with appropriate materials and advice. Despite these limitations, suggested promoting and emphasizing varied teaching approaches in classrooms.